If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(r+8)-r=-(5-r)
We move all terms to the left:
3(r+8)-r-(-(5-r))=0
We add all the numbers together, and all the variables
3(r+8)-r-(-(-1r+5))=0
We add all the numbers together, and all the variables
-1r+3(r+8)-(-(-1r+5))=0
We multiply parentheses
-1r+3r-(-(-1r+5))+24=0
We calculate terms in parentheses: -(-(-1r+5)), so:We add all the numbers together, and all the variables
-(-1r+5)
We get rid of parentheses
1r-5
We add all the numbers together, and all the variables
r-5
Back to the equation:
-(r-5)
2r-(r-5)+24=0
We get rid of parentheses
2r-r+5+24=0
We add all the numbers together, and all the variables
r+29=0
We move all terms containing r to the left, all other terms to the right
r=-29
| -7+8n=7n-8 | | 4x²-7x-2=0 | | -4/3-6/7x=-3/2 | | 156=6(4a-6)+8a | | | | 9v-6=75 | | -4(1-2n)=8n+1 | | 4x−12=2x3x−6 | | 2v+1=3 | | 4(3m-4)=3(m+9)+2 | | | | 18t=27 | | 13x+6-7x=42 | | 2.5n+10=n+1.5n-7 | | 52+6y=64 | | 2x=112-X=5X-8=180 | | w/5+4=6 | | −5x−4(4−2x)=4x−8 | | -98=-4(-3+5x)-2x | | 14x+18=36 | | 3x^2-1=48 | | -4b+6b=-34+20 | | 3b+3b=15 | | 5(2x-1)-6(x+1)=1 | | -5x-16=8x+3 | | 4x+65=180 | | 5(2xx1)=25 | | 4m+7=10m-11 | | 4-4n=43 | | 5x-(14-x)=-13-2x | | 4r+6r=20 | | 7+3y-2=8y+8-4y |